Quaternion Matrix Factorization for Low-Rank Quaternion Matrix Completion - Jiang-Feng Chen; Qing-Wen Wang; Guang-Jing Song; Tao Li (Mathematics, 2023)
The main aim of this paper is to study quaternion matrix factorization for low-rank quaternion matrix completion and its applications in color image processing. For the real-world color images, we proposed a novel model called low-rank quaternion matrix completion (LRQC), which adds total variation and Tikhonov regularization to the factor quaternion matrices to preserve the spatial/temporal smoothness. Moreover, a proximal alternating minimization (PAM) algorithm was proposed to tackle the corresponding optimal problem. Numerical results on color images indicate the advantages of our method.